1996
DOI: 10.1111/j.1469-7610.1996.tb01462.x
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Procedures and Attrition Containment in a Long‐Term Follow‐Up of a Community‐Based ADHD Sample

Abstract: Strategies are discussed for locating and interviewing a community-based sample of 492 adults, approximately half of whom were diagnosed in 1974 with ADHD. Completion rates, reasons for attrition, and amount of time and intensity of effort associated with subject location are reported. We found that 81% of the original sample had been located after 28 months, and that the reconstituted sample closely resembled the original larger childhood sample in background characteristics. Findings confirm that staff persi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…The pool of subjects interviewed during the adult followup initiated in 1992 ranged in age from 23 to 30 years, with an average age of 26n6 years. Moreover, it was demonstrated that there had not been selective attrition and that the reconstituted adult sample closely resembled the original larger childhood sample in childhood symptoms and background characteristics (Hartsough et al, 1996).…”
Section: Methods Subjectsmentioning
confidence: 98%
See 1 more Smart Citation
“…The pool of subjects interviewed during the adult followup initiated in 1992 ranged in age from 23 to 30 years, with an average age of 26n6 years. Moreover, it was demonstrated that there had not been selective attrition and that the reconstituted adult sample closely resembled the original larger childhood sample in childhood symptoms and background characteristics (Hartsough et al, 1996).…”
Section: Methods Subjectsmentioning
confidence: 98%
“…Local enforcement agencies in California have been required by law to report such arrests to the Bureau since 1973. These reports were, therefore, likely to be accurate representations of the current arrest-status of these adult subjects (Hartsough et al, 1996). The rap sheets yielded arrest records for 53 (23 %) of the 230 male subjects and 6 (8 %) of the female subjects in this sample.…”
Section: Methodsmentioning
confidence: 99%
“…Interviews with fieldwork experts in US survey research centers20 and descriptions of extended effort in the literature1,3,16,19,37 informed our definition of “hard to reach.” Because interviewers shared files and there was no strict order for the methods used to track respondents, we did not attempt to evaluate each tracking method separately. Instead, we used a summary measure.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, there is the issue of the source of the samples of children with ADHD studied in these investigations. With one exception in the published literature (i.e., Hartsough, Babinski, & Lambert, 1996), samples of ADHD youths are recruited from clinical sites. Because community-based ADHD youths are likely to reveal a less-severe form of ADHD (August, Realmuto, Crosby, & MacDonald, 1995), the association between childhood stimulant medication and later drug abuse may not be the same as among clinic-referred ADHD youths.…”
Section: Introductionmentioning
confidence: 99%